(3GdNW GdYQHj (B- (3fXQjI LeGdjI h MQaI jOhjI (B:s ((3eMGhdI dJCUjd LeGdj h GLJeGYj ddNW GdYQHj(B)s (Govt. of Sharjah; Dept. of Culture and Information, 2007)
12-30 April 2014
Title translation: "Arabic calligraphy - aesthetic theory and handicraft"
Arabic
Keywords: Calligraphy; NK1648-1678 Religious art